Associations among maternal socioeconomic status in childhood and pregnancy and hair cortisol in pregnancy. (January 2019) - Bosquet Enlow, Michelle; Sideridis, Georgios; Chiu, Yueh-Hsiu Mathilda; Nentin, Farida; Howell, Elizabeth A.; Le Grand, Blake A.; Wright, Rosalind J.
Highlights: First study to link life course SES to maternal hair cortisol in pregnancy. Lower maternal SES in childhood and pregnancy linked to higher cortisol levels. Childhood SES effects on pregnancy cortisol were mediated through SES in pregnancy. Effects were independent of race/ethnicity and pregnancy health measures. Maternal life course SES may have intergenerational effects via prenatal cortisol. Abstract: Dysregulation of the maternal-fetal hypothalamic-pituitary-adrenal axis (HPAA) has been hypothesized to negatively influence various offspring physical and mental health outcomes. Limited data suggest that low maternal socioeconomic status (SES) in pregnancy may disrupt maternal HPAA functioning. Research is needed that examines how maternal SES in childhood may influence maternal HPAA functioning in pregnancy, given evidence that early life adversity can have persistent effects on physiological stress reactivity. In a sample of 343 sociodemographically diverse women, we tested whether indices of life course SES were associated with HPAA functioning across pregnancy reflected in hair cortisol collected within one week after delivery. Mothers were asked whether their parent(s) owned their home across three developmental periods, from birth through adolescence, as an indicator of their childhood SES. Measures of maternal SES in pregnancy included maternal educational attainment, annual household income, and current homeownership. Analyses revealed that indicators of lower maternal SES in childhood and in pregnancy were associated with higher cortisol levels during each trimester. In analyses adjusted for maternal race/ethnicity, pre-pregnancy body mass index, smoking in pregnancy, use of inhaled and topical corticosteroids, and mode of delivery, each indicator of maternal SES in pregnancy fully mediated maternal childhood SES effects on maternal hair cortisol levels in pregnancy. This is the first study to show an association between maternal life course SES and hair cortisol in pregnancy. The results suggest that maternal SES, starting in childhood, may have intergenerational consequences via disruption to the maternal-fetal HPAA in pregnancy. These findings have implications for elucidating mechanisms contributing to health disparities among socioeconomically disadvantaged populations.